A rare case of rectal malignant melanoma with long-term survival: case report and literature review - Haitao Huang; Yanquan Liu; Hai Xiao; Jiachen Xie; Yiqun Kang; Ye Li; Huidong Guo (World Journal of Surgical Oncology)
Abstract Background Although cutaneous melanoma is relatively common, rectal malignant melanoma is extremely rare. Due to its rarity, rectal malignant melanoma is often not considered in the initial differential diagnosis. In such clinical scenarios, avoiding misdiagnosis, achieving early detection, and providing appropriate treatment remain major challenges and require particular attention. This case report presents a detailed account of the diagnostic and therapeutic process in a patient with primary rectal malignant melanoma. By sharing this case, we aim to provide clinicians with practical experience and valuable insights, thereby enhancing awareness and understanding of this rare condition within the medical community. Case presentation A 56-year-old female presented to the hospital with a 10-day history of a perianal mass and hematochezia. Physical examination revealed a soft, flat abdomen with no palpable masses and normal bowel sounds. Imaging findings showed localized thickening of the distal rectum, diffuse mild thickening of the mid-to-upper rectal wall, and multiple small lymph nodes in the sigmoid mesocolon.Postoperative histopathological analysis, supported by immunohistochemical staining, confirmed the diagnosis of malignant melanoma. The patient underwent laparoscopic Miles surgery, followed by adjuvant abdominopelvic radiotherapy (GTVtb 50 Gy, CTV45 Gy) and targeted therapy with tislelizumab. She had an uneventful recovery and remained free of disease progression during 48 months of follow-up. Conclusions This case of rectal malignant melanoma, incidentally diagnosed during hemorrhoidectomy, was successfully treated with laparoscopic Miles’ procedure and targeted immunotherapy, resulting in long-term disease-free survival, thereby raising clinical awareness and providing valuable insights for managing similar cases.